INDIVIDUAL SPECIES AREA RELATIONSHIP OF TROPICAL TREE SPECIES AFTER SELECTIVE LOGGING REGIMES IN TRUONG SON FOREST ENTERPRISE, QUANG BINH PROVINCE - Hong Hai, Nguyen; Minh Quang, Nguyen (Journal of Forestry Science and Technology, 2019)
Explaining the high diversity of tropical rain forest has been a challenge for ecologists for decades. We applied a recent technique of spatial statistics that is Individual species area relationship (ISAR) to study diversity structure of a tropical broadleaved forest based on individual species. The ISAR is combined by species area relationship and Ripley’s K to measure the expected a diversity of individual specific species in circular neighborhoods with variable radius of moving window circles around an arbitrary individual of a focal species. Data was collected from two fully mapped 2-ha plots of tropical broadleaved forest in Quang Binh province, Vietnam. Tree species with at least 30 individuals/species were analyzed. It was found that 21 of 53 species were diversity significant at probability of 0.05 in both study plots. In which, five diversity accumulators and five diversity repellers were identified in P1; 11 species were regarded to diversity accumulators in P2 at various spatial scales. Most of signatures on spatial diversity were mainly found at scales smaller than 30 m, while some were found at larger scales. Species diversity was assumed to be unaffected by tree size or species abundance. Effect of logging regimes on species diversity showed by lower number of accumulators and higher number of repellers with conventional logging (P1) than reduced impact logging (P2). Beside effect of logging regimes, the ecological processes such as dispersal limitation, species herd protection and scale separation were inferred as the main drivers regulating spatial diversity patterns of the studied forest stands.